Effect of Using a Solar Can Heater Collector on the Temperature of a Room at Several External Temperature Variations - Willy Vernando; Andre Kurniawan; Refdinal Refdinal; Yolli Fernanda (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
This research discusses a heating collector device which functions to warm a room that has a relatively cold temperature so as to create thermal comfort. Thermal comfort greatly influences human performance in activities in a room so that effective performance in a room can be achieved. This collector functions to collect solar heat and increase the temperature of the sun's heat which will then be channeled into a closed room. This collector is in the form of a box measuring 750x450 mm. This collector consists of cans arranged vertically which are useful as a medium for capturing heat and increasing solar heat. The measurement results show that the room heater can warm a cold room at a temperature of 22.4⁰C to 28.2⁰C. and the air heating capacity obtained is 0.24 kJ to 4.58 kJ. Penelitian ini membahas tentang alat kolektor pemanas yang berfungsi untuk menghangatkan ruangan yang memiliki suhu relatif dingin sehingga terciptanya kenyamanan termal. Kenyamanan termal sangat berpengaruh terhadap kinerja manusia dalam beraktifitas di dalam suatu ruangan sehingga dapat tercapai efektifitas kinerja di dalam suatu ruangan. Kolektor ini berfungsi mengumpulkan panas matahari serta memperbesar suhu dari panas matahari yang nantinya akan di alirkan ke suatu ruangan yang tertutup. Kolektor ini berbentuk boks yang berukuran 750x450 mm,kolektor ini terdiri dari kaleng yang disusun secara vertical yang berguna untuk media penangkap panas dan memperbesar panas matahari. Hasil pengukuran menunjukkan bahwa pemanas ruangan dapat menghangatkan ruangan yang dingin pada suhu 22,4⁰C menjadi 28,2⁰C. dan kapasitas pemanas udara yang diperoleh adalah 0,24 kj hingga 4,58 kj.